2016
DOI: 10.1186/s13073-016-0298-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the fecal microbiome in patients with recurrent and nonrecurrent Clostridium difficile infection

Abstract: BackgroundRecurrent Clostridium difficile infection (CDI) remains problematic, with up to 30 % of individuals diagnosed with primary CDI experiencing at least one episode of recurrence. The success of microbial-based therapeutics, such as fecal microbiota transplantation, for the treatment of recurrent CDI underscores the importance of restoring the microbiota. However, few studies have looked at the microbial factors that contribute to the development of recurrent disease. Here we compare microbial changes ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 40 publications
12
109
0
Order By: Relevance
“…Indeed, recent studies of CDI in humans have found that decreased microbial diversity is associated with severe and recurrent CDI (51) and have also identified patterns of microbiota change associated with recovery from CDI (52). Antibiotic exposure is the primary risk factor for the development of symptomatic CDI because this treatment perturbs the gut microbiota and reduces colonization resistance (50).…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%
“…Indeed, recent studies of CDI in humans have found that decreased microbial diversity is associated with severe and recurrent CDI (51) and have also identified patterns of microbiota change associated with recovery from CDI (52). Antibiotic exposure is the primary risk factor for the development of symptomatic CDI because this treatment perturbs the gut microbiota and reduces colonization resistance (50).…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%
“…38 In addition, recently two studies have identified microbiome signatures that allow prediction of disease outcome allowing therapeutic stratification. 39, 40 An expansion of Proteobacteria in the setting of dysbiotic microbiota was described in patients with celiac disease with gastrointestinal symptoms compared to those with extra-intestinal manifestations of celiac disease. 41 In addition to diseases within gastrointestinal tract, it is interesting that several studies have described gut microbiome signatures in systemic disorders such as rheumatoid arthritis.…”
Section: Microbiome As a Tool For Precision Diagnosis And Personalizementioning
confidence: 99%
“…Its excellent clinical efficacy is further upheld by the observation that host intestinal microbiota composition and diversity are intimately linked to CDI severity and recurrence risk [205]. …”
Section: Restoration and Modulation Of The Intestinal Microbiotamentioning
confidence: 99%